An Islamic monetary theory of value and equation of exchange: evidence from Egypt (696–1517) - Abdullah, Adam (Emerald Group Publishing, 2016)
Purpose - The purpose of this research is to present an Islamic monetary theory of value by analyzing real prices and real money in terms of gold and silver in Egypt from 696-1517, a period of 821 years from the Umayyads to the Abbasids. Design/methodology/approach - It adopts a quantitative empirical investigation derived from a full population of secondary data to deductively evaluate the measure and store of value functions of money, to affirm an Islamic monetary theory of value, which is also inductively researched through a qualitative interpretation of documentary and content analysis of Islamic and numismatic literature. Findings - The Islamic monetary theory of value leads to an Islamic equation of exchange that reconfirms the outcome of this research, where a high value of money ensures low constant real prices over the long term. Research limitations/implications - The findings are based on an empirical investigation involving a single price of wheat series as a reasonable proxy for changes in wholesale commodity prices generally, which was successfully adopted by other studies. Practical implications - The significance for modern monetary policy is that monetary authorities should adopt an Islamic monetary theory of value to achieve genuine monetary and price stability. Social implications - Through an Islamic equation of exchange, price stability would ensure real economic growth that protects wealth for holders of money due to a stable purchasing power, and combined with Islamic equity finance is more efficient in allocating investible resources to increase GDP and employment. Originality/value - The Islamic monetary theory of value ensures that there is no transfer or confiscation of wealth through inflation, which would impart gains to the issuer due to the excessive supply of money in relation to demand.